Equality within our lifetimes : how laws and policies can close-or widen-gender gaps in economies worldwide - Heymann, Jody, 1959-; Sprague, Aleta, 1986-; Raub, Amy, 1981- (University of California Press, 2023)
"The book proceeds in three sections. In section one, we examine how the laws in every country address discrimination in the workplace-not only on the basis of sex and gender, but also based on pregnancy, family status, race/ethnicity, religion, disability, migration status, sexual orientation, socioeconomic status, and gender identity. Section 2 explores why achieving gender equality in the economy will be impossible without addressing both paid and unpaid caregiving. Lastly, in section three, we assess what it takes to make change happen. Section three examines approaches that would make a difference within months as well as approaches that would be transformational long-term"-- Provided by the publisher.
Keywords: Equality before the law.; Sex discrimination against women.; Equality -- Economic aspects.; Sexual harassment of women -- Economic aspects.; Sex discrimination -- Economic aspects.; Discrimination in employment.; Discrimination in employment -- Law and legislation.; Sex discrimination in employment.; Sex discrimination in employment -- Law and legislation.; Égalité devant la loi.; Discrimination sexuelle -- Aspect économique.; Discrimination dans l'emploi.; Discrimination sexuelle dans l'emploi.; Discrimination à l'égard des femmes.; Harcèlement sexuel -- Aspect économique.; LAW / Gender & the Law.; Sex discrimination in employment -- Law and legislation; Discrimination in employment -- Law and legislation; Discrimination in employment; Equality before the law; Equality -- Economic aspects; Sex discrimination in employment; Electronic books.